Too soon to say good-bye - Kent, Deborah; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1996)
Diagnosed with leukemia after a fainting spell, young Jill copes with painful therapy, being treated differently by her family and peers, and facing the frightening possibility that she will die.
"An Apple paperback."
Keywords: Leukemia -- Juvenile fiction; Cancer -- Fiction